Detecting snowboarding moves with sensorized bindings - Holleczek, T.; Rüegg, A.; Harms, H.; Tröster, G. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: Requiring complex motion sequences, snowboarding is difficult to learn and improving one's skills often requires lessons given by an experienced teacher. Yet even this approach has its limitations, as instructors might not notice all mistakes. We have therefore been developing a wearable trainer capable of supporting snowboarders in improving their riding style [1,2]. Such trainers are built on sensor systems recognizing the activities performed by its users. In snowboarding, traditional activity recognition approaches make use of insoles with force-sensitive resistors (FSRs), which, however, are particularly uncomfortable to wear. In this paper, we show how FSRs can be integrated into snowboard bindings and how basic snowboarding moves such as turns and the riding edge can be recognized with the algorithm Nearest Centroid Classifier (NCC) from the sensor data.